Seismic risk assessment of algerian buildings in urban area - Baba Hamed, Fatima Zohra; Rahal, Driss Djaouad; Rahal, Farid (Journal of Civil Engineering and Management, 2013)
The recent earthquakes in Algeria have caused significant human and economic losses. The frequent occurrence of damaging earthquakes clearly demonstrates the urgent need of study on seismic risk assessment methods of buildings to effectively reduce the impact of earthquake in Algerian cities. This article contributes to the development and the application of a seismic risk method, appropriate to Algerian building specificities. This method considers five damage levels, defined accordingly to macroseismic intensity and the seismic quality of the building by means of a vulnerability index. The present paper summarises the development of a tool to integrate seismic hazard and structural information and support the decision making process in identification of seismic risk. This tool could be used in the inspection of buildings and the optimal prioritisation of strengthening and preventives remedial actions that are necessary prior to a major earthquake event.